Peningkatan Hasil Belajar dan Keaktifan Siswa dalam Pembelajaran Matematika Melalui Penggunaan Media Konkret di Kelas 1 Madrasah Ibtidayah Negeri 3 Sarolangun - Hasuna Maya; Thomas Wildan Nugraha; Hasrudi Adinata (Peneliti.net, 2026)
This classroom action research was conducted to improve first-grade students’ learning outcomes and learning activeness in mathematics through the use of concrete media at MIN 3 Sarolangun. The study was motivated by low student participation and low achievement in learning addition and subtraction of numbers from 1 to 20. The research applied a two-cycle classroom action research design consisting of planning, action, observation, and reflection stages. The subjects were 20 first-grade students. Data were collected through observation sheets, learning outcome tests, and field notes, then analyzed using quantitative and qualitative approaches. The results showed a significant improvement in both student activeness and learning outcomes. Student activeness increased from 29% in the pre-cycle to 73% in Cycle I and 90% in Cycle II. The average test score improved from 61 in the pre-cycle to 70 in Cycle I and 78 in Cycle II, with classical mastery reaching 95% in Cycle II. The findings indicate that the use of concrete media effectively enhances student engagement and mathematics learning outcomes, especially for early grade learners who are in the concrete operational stage. Therefore, the integration of concrete learning media is recommended to support more active and meaningful mathematics instruction in primary education.